Photo-thermal catalyst, preparation method thereof and application of photo-thermal catalyst in carbon dioxide hydrogenation reaction

Multi-layer Ti3C2Tx support was prepared by hydrofluoric acid etching method, and Ru/ML-Ti3C2Tx photothermal catalyst was prepared by solution ion electrostatic adsorption method, which solved the problem of insufficient stability and heat management capabilities of the existing MXene-based photothermal catalysts, and achieved efficient and stable photothermal catalytic carbon dioxide hydrogenation reaction.

CN119746896APending Publication Date: 2025-04-04SUZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510014270.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing MXene-based photothermal catalysts are insufficient in stability during long-term reactions, lack of heat management capabilities, long preparation cycles and low yields, making it difficult to meet actual production needs.

Method used

Multi-layer Ti3C2Tx with an accordion-like microstructure of more than 15 layers were prepared as a support by hydrofluoric acid etching method. Ru/ML-Ti3C2Tx photothermal catalyst was prepared by solution ion electrostatic adsorption method.

Benefits of technology

It has achieved nearly twice the improvement of heat management capabilities, significantly improving the stability and catalytic activity of photothermal catalysts, simplifying the preparation process, reducing production costs, and suitable for large-scale applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746896A_ABST
    Figure CN119746896A_ABST
Patent Text Reader

Abstract

The invention discloses a photo-thermal catalyst, a preparation method thereof and an application of the photo-thermal catalyst in a carbon dioxide hydrogenation reaction, an ML-Ti3C2Tx photo-thermal catalyst carrier is prepared from a Ti3AlC2 raw material through a one-step hydrofluoric acid etching method, and then Ru is loaded on the surface and an interlayer of the ML-Ti3C2Tx through a solution ion electrostatic adsorption method. The Ru / ML-Ti3C2Tx photo-thermal catalyst with high heat management capability and excellent stability is prepared, so that stable and high-activity photo-thermal catalytic carbon dioxide hydrogenation reaction is realized. The Ru / ML-Ti3C2Tx photo-thermal catalyst provided by the invention has a multi-layer microstructure, and heat radiation and heat conduction are effectively reduced by the catalyst through rich low-heat-conductivity air between layers, so that nearly twice improvement of heat management capability is realized, and the effect of optimizing photo-thermal catalytic performance is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photothermal catalytic materials, and in particular to a photothermal catalyst and a preparation method thereof, and application thereof in a carbon dioxide hydrogenation reaction. Background Art

[0002] Carbon dioxide is one of the main greenhouse gases that cause global warming. Carbon dioxide conversion technology can be used to convert it into high-value chemicals, thereby slowing down the trend of global warming. Traditional carbon dioxide conversion technology mainly relies on thermal energy provided by fossil energy. This process not only increases greenhouse gas emissions, but also exacerbates the problem of energy shortage. Therefore, it is particularly important to develop new, green and efficient carbon dioxide conversion technology.

[0003] Photothermal catalytic carbon dioxide hydrogenation technology is a new green conversion technology with potential. It uses solar energy as energy and converts carbon dioxide into high-value-added fuels through the action of photothermal catalysts, which helps to reduce human dependence on fossil energy and improve energy efficiency. It is of great significance for achieving sustainable development. However, the development of photothermal catalytic technology is limited by the performance of photothermal catalysts. Efficient photothermal catalysts must have high light absorption performance and photothermal conversion efficiency, excellent heat management ability, high surface reaction activity and reaction stability. Two-dimensional MXene materials have great application potential in the field of photothermal catalysis due to their excellent light absorption and photothermal conversion performance. Researchers have tried to use MXene as a catalyst carrier to load active metals to achieve efficient photothermal catalysis. However, although MXene-based photothermal catalysts have many advantages in theory, they still face many challenges in practical applications.

[0004] The lack of stability in the photothermal catalytic carbon dioxide conversion reaction is a major bottleneck of current technology. Many existing MXene-based photothermal catalysts are prone to performance degradation during long-term reactions, making it difficult to meet the needs of actual production. For example, although the W18O49 / Nb2C MXene photothermal catalytic material disclosed in CN118847175A has improved the conversion rate and selectivity of carbon dioxide to a certain extent, it does not emphasize the stability of the catalyst in photothermal catalysis. In addition, the insufficient heat management ability of thin-layer MXene materials is also a key factor restricting the improvement of photothermal catalytic performance. Due to the small number of MXene nanosheets, heat dissipation is faster, making it difficult to maintain efficient temperature control during photothermal catalysis. For example, the MXene composite material modified with a ruthenium complex disclosed in CN115590956A combines photothermal and photodynamic effects, but the ultra-thin MXene nanosheets have poor heat management capabilities and are prone to close stacking under strong light irradiation, resulting in a significant decrease in catalyst stability. In addition, the long preparation cycle and low yield of MXene-based photothermal catalysts are also problems that current technology urgently needs to solve. This not only increases production costs, but also limits the large-scale application of photothermal catalytic technology.

[0005] Therefore, developing new, efficient and stable MXene-based photothermal catalysts and optimizing their preparation processes are of great significance for promoting the development of photothermal catalytic technology. Summary of the invention

[0006] In order to solve the above technical problems, the present invention provides a photothermal catalyst and a preparation method thereof and application in carbon dioxide hydrogenation reaction.

[0007] The present invention is achieved through the following technical solutions:

[0008] The present invention provides a method for preparing a photothermal catalyst, comprising the following steps:

[0009] (1) Ti 3 AlC 2 The powder is mixed with a hydrofluoric acid solution and etched to obtain a multilayer Ti with more than 15 layers of acidity. 3 C 2 T x The solution was centrifuged to collect the precipitate, washed until neutral, and the washed precipitate was dispersed in water to obtain a multilayer Ti 3 C 2 T x (Muti-layer Ti 3 C 2 T x ,ML-Ti 3 C 2 T x) solution; wherein T is one or more of -O, -F and -OH;

[0010] (2) Under the protection of inert gas, the trivalent ruthenium salt and the multilayer Ti obtained in step (1) are mixed. 3 C 2 T x The solution is mixed, and the obtained mixed solution is dried to obtain the photothermal catalyst (Ru / ML-Ti 3 C 2 T x ).

[0011] The present invention uses a one-step hydrofluoric acid etching method to remove the 3 AlC 2 ML-Ti was prepared from raw materials 3 C 2 T x Photothermal catalyst support, ML-Ti 3 C 2 T x Refers to Ti with an accordion-like microstructure of more than 15 layers 3 C 2 T x ; Then Ru was loaded on ML-Ti by solution ion electrostatic adsorption method 3 C 2 T x The Ru / ML-Ti with strong thermal management ability and excellent stability was prepared on the surface and interlayer of 3 C 2 T x Photothermal catalysts to achieve stable and highly active photothermal catalytic carbon dioxide hydrogenation reactions.

[0012] Further, in step (1), the Ti 3 AlC 2 The dosage ratio of powder to hydrofluoric acid solution is (0.8-1.5) g: (10-15) mL.

[0013] Furthermore, in step (1), the etching time is 8-12 hours.

[0014] In a specific embodiment, in step (1), Ti 3 AlC 2 The powder is mixed with hydrofluoric acid solution and etched to obtain acidic multilayer Ti 3 C 2 T x The solution was centrifuged at a speed of 1500-2000 r / min to collect the precipitate, which was washed with water until the pH value of the supernatant was about 7. Water was added to dilute the precipitate to obtain ML-Ti 3 C 2 Tx Solution.

[0015] Furthermore, in step (2), the trivalent ruthenium salt is ruthenium trichloride (RuCl 3 ).

[0016] Furthermore, in step (2), the mass of the ruthenium element in the trivalent ruthenium salt accounts for 3 C 2 T x Multilayer Ti in solution 3 C 2 T x 1-10% by mass, preferably 5-10%.

[0017] Furthermore, in step (2), the multilayer Ti 3 C 2 T x The concentration of the solution is 1-5 mg / mL.

[0018] Furthermore, in step (2), the drying treatment conditions are: vacuum drying at 70-80°C for 6-7h.

[0019] In a specific embodiment, in step (2), a trivalent ruthenium salt is reacted with the ML-Ti obtained in step (1) 3 C 2 T x The solutions were mixed and stirred for 3-4 hours under inert gas protection to allow Ru ions to adsorb on the ML-Ti 3 C 2 T x The obtained mixed solution was then dried under vacuum at 70-80°C for 6-7h to obtain Ru / ML-Ti 3 C 2 T x Photothermal catalyst powder.

[0020] The present invention protects a photothermal catalyst prepared by the above method.

[0021] The present invention also protects an application of the above-mentioned photothermal catalyst in a carbon dioxide hydrogenation reaction, mainly used for a photothermal catalytic carbon dioxide hydrogenation reaction.

[0022] Furthermore, a photothermal catalytic testing device is used to perform a performance test on the photothermal catalyst, wherein the photothermal catalytic testing device is composed of a xenon lamp light source, a kettle reactor, a reaction gas inlet, a heating module, a heat preservation module, a reaction gas outlet and a temperature measurement module.

[0023] Beneficial effects of the present invention:

[0024] 1. Ru / ML-Ti provided by the present invention 3 C2 T x The photothermal catalyst has a multi-layer microstructure. The catalyst effectively reduces thermal radiation and heat conduction through abundant low-thermal conductivity air between layers, thereby achieving a nearly two-fold improvement in heat management capabilities, thereby achieving the effect of optimizing photothermal catalytic performance.

[0025] 2. The preparation method of the photothermal catalyst provided by the present invention is simple and has a short preparation cycle, which is conducive to future large-scale production.

[0026] 3. The photothermal catalytic testing method proposed in the present invention has the advantages of high light utilization, sufficient heat energy preservation, and maximized contact area between reaction gas and catalyst, which significantly improves the catalytic efficiency and provides new insights for the design of future photothermal catalytic devices.

[0027] 4. Ru / ML-Ti provided by the present invention 3 C 2 T x The photothermal catalyst showed excellent long-term stability in the photothermal catalytic carbon dioxide hydrogenation reaction at 2000mW / cm 2 Under simulated sunlight, it is possible to achieve a methane selectivity of nearly 95.2% while maintaining a carbon dioxide conversion rate of about 42.2%, which is close to actual production needs. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The Ru / ML-Ti prepared in Example 1 3 C 2 T x Photothermal catalyst and Ru / FL-Ti prepared in Comparative Example 1 3 C 2 T x XRD patterns of the photothermal catalysts.

[0029] Figure 2 The Ru / ML-Ti prepared in Example 1 3 C 2 T x Photothermal catalyst and Ru / FL-Ti prepared in Comparative Example 1 3 C 2 T x SEM image of the photothermal catalyst.

[0030] Figure 3 The Ru / ML-Ti prepared in Example 1 3 C 2 T x TEM image of the photothermal catalyst and its elemental mapping.

[0031] Figure 4Schematic diagram of the photothermal catalytic test device.

[0032] Figure 5 The Ru / ML-Ti prepared in Example 1 3 C 2 T x Photothermal catalyst and Ru / FL-Ti prepared in Comparative Example 1 3 C 2 T x Infrared camera cooling curve of photothermal catalyst.

[0033] Figure 6 The Ru / ML-Ti prepared in Example 1 3 C 2 T x Photothermal catalyst and Ru / FL-Ti prepared in Comparative Example 1 3 C 2 T x The catalytic performance test results of photothermal catalysts used in photothermal catalytic carbon dioxide hydrogenation reaction.

[0034] Figure 7 The Ru / ML-Ti prepared in Example 1 3 C 2 T x Figure 3. Stability test results of photothermal catalyst used in photothermal catalytic carbon dioxide hydrogenation reaction.

[0035] Explanation of the reference numerals: 1. xenon lamp light source, 2. quartz cover, 3. kettle reactor, 4. reaction gas inlet, 5. heating wire, 6. insulation layer, 7. generated gas outlet, 8. temperature measuring thermocouple, 9. catalyst. DETAILED DESCRIPTION

[0036] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0037] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0038] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods, and the materials, reagents, etc. used are all available from commercial sources unless otherwise specified.

[0039] Example 1

[0040] A Ru / ML-Ti 3 C 2 T x Photothermal catalyst (5% Ru / ML-Ti 3 C 2 T x ), comprising the following steps:

[0041] (1) 1g Ti 3 AlC 2 The powder was mixed with 15 mL of 49% hydrofluoric acid solution and allowed to stand for 12 h before etching to obtain an acidic multilayer Ti 3 C 2 T x Then, the precipitate was collected by centrifugation and washed with deionized water, wherein the centrifugal speed was 2000 r / min, until the pH value of the supernatant was about 7, and then deionized water was added to the precipitate to dilute it to a concentration of 5 mg / mL to obtain ML-Ti 3 C 2 T x Solution.

[0042] (2) RuCl 3 Powder and ML-Ti 3 C 2 T x The solutions were mixed and stirred for 4 h under nitrogen protection, wherein the mass of ruthenium element accounted for ML-Ti 3 C 2 T x The obtained mixed solution was then dried under vacuum at 80 °C for 6 h to obtain Ru / ML-Ti 3 C 2 T x Photothermal catalyst.

[0043] Example 2

[0044] A Ru / ML-Ti 3 C 2 T x Photothermal catalyst (1% Ru / ML-Ti 3 C 2 T x ) is basically the same as in Example 1, except that in step (2), the mass of ruthenium element accounts for ML-Ti 3 C 2 T x 1% of mass.

[0045] Example 3

[0046] A Ru / ML-Ti 3 C2 T x Photothermal catalyst (10% Ru / ML-Ti 3 C 2 T x ) is basically the same as in Example 1, except that in step (2), the mass of ruthenium element accounts for ML-Ti 3 C 2 T x 10% of mass.

[0047] Comparative Example 1

[0048] A Ru / FL-Ti 3 C 2 T x The method for preparing a photothermal catalyst comprises the following steps:

[0049] (1) 1g Ti 3 AlC 2 The powder was mixed with 15 mL of 49% hydrofluoric acid solution and allowed to stand for 12 h before etching to obtain an acidic multilayer Ti 3 C 2 T x Then, the precipitate was collected by centrifugation and washed with deionized water, wherein the centrifugal speed was 2000r / min until the pH value of the supernatant was about 7, thereby obtaining ML-Ti 3 C 2 T x precipitation.

[0050] (2) Add 10 mL of 1 mg / mL tetramethylammonium hydroxide solution to the ML-Ti obtained in step (1) 3 C 2 T x During the precipitation, ultrasonic treatment was performed for 10 minutes every 12 hours, and an alkaline mixed solution was obtained after 48 hours. In this process, tetramethylammonium hydroxide played a microscopic peeling role. Subsequently, the alkaline mixed solution was washed with deionized water to a pH value of about 8, centrifuged at a speed of 3000 r / min, and the supernatant was taken to obtain FL-Ti with a concentration of about 5 mg / mL. 3 C 2 T x Solution.

[0051] (3) RuCl 3 Powder and FL-Ti 3 C 2 T x The solutions were mixed and stirred for 4 h under nitrogen protection, wherein the mass of ruthenium element accounted for 1.3% of FL-Ti 3 C 2 T xThe obtained mixed solution was then dried under vacuum at 80 °C for 6 h to obtain Ru / FL-Ti 3 C 2 T x Photothermal catalyst.

[0052] Comparative Example 1: Ru / FL-Ti was prepared by electrostatic adsorption 3 C 2 T x Photothermal catalyst, where FL is Few-Layer, FL-Ti 3 C 2 T x Refers to Ti with 1-3 layers of microstructure 3 C 2 T x Comparative Example 1: Preparation of a few-layer FL-Ti by adding a peeling step 3 C 2 T x Photothermal catalyst, as a comparison of multilayer photothermal catalysts.

[0053] Test Example 1

[0054] The Ru / ML-Ti prepared in Example 1 was analyzed by X-ray diffractometer (XRD). 3 C 2 T x Photothermal catalyst and Ru / FL-Ti prepared in Comparative Example 1 3 C 2 T x The photothermal catalyst was characterized, and the characterization results are as follows Figure 1 As shown, Ru / ML-Ti 3 C 2 T x Photothermal catalyst and Ru / FL-Ti 3 C 2 T x The diffraction peak before 10° in the XRD pattern of the photothermal catalyst corresponds to Ti 3 C 2 T x The longitudinal lattice spacing between the layers in the structure. The farther the position of the diffraction peak is from 0°, the closer the Ti 3 C 2 T x The smaller the interlayer spacing, the more layers there are. Figure 1 Ru / ML-Ti 3 C 2 T x The diffraction peak of the photothermal catalyst is farther away from 0°, indicating that it has more layers and a multi-layer structure.

[0055] The Ru / ML-Ti prepared in Example 1 was examined by scanning electron microscopy (SEM). 3 C 2 T x Photothermal catalyst and Ru / FL-Ti prepared in Comparative Example 1 3 C 2 T x The photothermal catalyst was characterized for morphology. Figure 2 As shown, from Figure 2 Ru / ML-Ti can be directly observed in 3 C 2 T x The photothermal catalyst has an accordion-like multilayer structure with more than 15 layers, and Ru / FL-Ti 3 C 2 T x Photothermal catalysts have only a thin layer structure with a very small number of layers.

[0056] The Ru / ML-Ti prepared in Example 1 was examined by transmission electron microscopy (TEM). 3 C 2 T x The photothermal catalyst was characterized and its element mapping was tested. The test results are as follows Figure 3 As shown, Figure 3 It shows that Ru metal is evenly dispersed in ML-Ti 3 C 2 T x In the carrier.

[0057] Test Example 2

[0058] The Ru / ML-Ti prepared in Examples 1-3 was tested using a photothermal catalytic test device. 3 C 2 T x Photothermal catalyst and Ru / FL-Ti prepared in Comparative Example 1 3 C 2 T x Photothermal catalyst performance test.

[0059] Schematic diagram of the photothermal catalytic test device Figure 4 As shown, the device mainly consists of a xenon lamp light source 1, a kettle reactor 3 (also including a quartz cover 2), a reaction gas inlet 4, a heating module (heating wire 5), a heat preservation module (heat preservation layer 6), a reaction gas outlet 7, and a temperature measurement module (temperature measurement thermocouple 8). In the photothermal catalytic test, the xenon lamp light source 1 simulates sunlight to irradiate the surface of the catalyst 9, the catalyst 9 heats up rapidly, the reaction gas enters from the reaction gas inlet 4 and flows down, fully contacts the catalyst 9 in the glass fiber filter paper, and a catalytic reaction occurs. Finally, the reaction gas is collected through the lower conical cavity and enters the gas chromatograph for detection.

[0060] 1. Test of Ru / ML-Ti prepared in Example 1 3 C 2 T x Photothermal catalyst and Ru / FL-Ti prepared in Comparative Example 1 3 C 2 T x Infrared camera cooling curve of photothermal catalyst.

[0061] The test method is: dissolve 15 mg of photothermal catalyst in 1 mL of ethanol solution, drop the mixed solution on a circular porous glass fiber filter paper, dry it at 70°C, and wait for the photothermal catalyst to be evenly distributed on the glass fiber filter paper. Figure 4 In the reactor shown in FIG. 2 Because infrared light cannot pass through the quartz cover above the reactor 100%, the infrared camera is calibrated for infrared transmittance before formal testing. The specific steps are as follows: Heat the quartz reactor so that the catalyst surface temperature (T 实际 ) reached 350℃, 360℃, 370℃, 380℃, 390℃, and 400℃ respectively. After the catalyst surface temperature measured by the thermocouple stabilized, the catalyst surface temperature (T 观察 ) are 154℃, 158.5℃, 162.8℃, 167.5℃, 171.6℃, and 176℃ respectively. The infrared light transmittance calculation formula is n 透过= T 观察 / T 实际 By calculating the average value of five calibration tests, it is found that the infrared transmittance of the quartz cover is about 0.44. At the beginning of the formal test, the infrared camera transmittance parameter is set to 0.44, and the light intensity of the xenon light source is adjusted to make the surface temperature of the photothermal catalyst reach 370℃. After the temperature stabilizes, the light source is turned off, and the infrared camera records the surface temperature drop of the photothermal catalyst in real time.

[0062] Test results such as Figure 5 As shown, it is found that the Ru / FL-Ti 3 C 2 T x The photothermal catalyst took 11 s, while Ru / ML-Ti 3 C 2 T x The photothermal catalyst took 23s, and the slower cooling rate indicated that Ru / ML-Ti 3 C 2 T x Photothermal catalysts have a better ability to retain thermal energy, that is, better thermal management capabilities.

[0063] 2. Test of Ru / ML-Ti prepared in Examples 1-3 3 C 2 T x Photothermal catalyst and Ru / FL-Ti prepared in Comparative Example 1 3 C 2 T x The catalytic performance of photothermal catalysts used in photothermal catalytic carbon dioxide hydrogenation reaction.

[0064] The test method is: dissolve 15 mg of photothermal catalyst in 1 mL of ethanol solution, drop the mixed solution on a circular porous glass fiber filter paper, dry it at 70 ° C, and wait for the photothermal catalyst to be evenly distributed on the glass fiber filter paper. Figure 4 In the reactor shown in the figure, H was introduced at a flow rate of 20 mL / min. 2 The reactor was heated to 400 °C at a rate of 10 °C / min by programmed temperature increase and kept at this temperature for 1 h to reduce the Ru oxide in the photothermal catalyst to metallic Ru. 2 The reactor was protected and cooled to room temperature. CO was introduced into the reactor at a total flow rate of 20 mL / min. 2 , H 2 、N 2 Mixed gas, the ratio is CO 2 :H 2 :N 2 =2:8:10. Adjust the xenon lamp intensity to 1000mW / cm 2 , irradiated on the surface of the photothermal catalyst, and the gas products of the reaction were detected using a gas chromatograph.

[0065] The test results are shown in Table 1 and Figure 6 As shown:

[0066] Table 1 Ru / ML-Ti prepared in Examples 1-3 3 C 2 T x Catalytic performance data table of photothermal catalysts

[0067] catalyst <![CDATA[CO 2 Conversion rate (%)]]> <![CDATA[CH 4 Selectivity (%)]]> <![CDATA[1%Ru / ML-Ti 3 C 2 T x ]]> 4.1 65.3 <![CDATA[5%Ru / ML-Ti 3 C 2 T x ]]> 13.1 95.4 <![CDATA[10%Ru / ML-Ti 3 C 2 T x ]]> 12.6 95.2

[0068] It can be seen from Table 1 that at 1000mW / cm 2 Under simulated solar irradiation, the photothermal catalyst with a loading of 5% showed the best performance, i.e., the highest CO 2 Conversion degree and the highest CH 4 Selective.

[0069] Figure 6 The Ru / ML-Ti prepared in Example 1 3 C 2 Tx Photothermal catalyst and Ru / FL-Ti prepared in Comparative Example 1 3 C 2 T x The catalytic performance test results of the photothermal catalyst used in the photothermal catalytic carbon dioxide hydrogenation reaction are shown in Figure 1. 2 Under simulated solar irradiation, Ru / ML-Ti 3 C 2 T x The photothermal catalyst showed a better performance than Ru / FL-Ti 3 C 2 T x The photothermal catalyst has better photothermal carbon dioxide hydrogenation performance, reaching a carbon dioxide conversion rate of 12.5% ​​and a methane selectivity of 95%. 3 C 2 T x The performance of the photothermal catalyst decreased within 1.5 h of reaction, while Ru / ML-Ti 3 C 2 T x The photothermal catalyst was able to remain stable while its performance slightly increased, indicating that it has better stability in photothermal catalysis.

[0070] 3. The Ru / ML-Ti prepared in Example 1 3 C 2 T x The photothermal catalyst was used to conduct stability test on the photothermal catalytic carbon dioxide hydrogenation reaction.

[0071] The test method is: dissolve 15 mg of photothermal catalyst in 1 mL of ethanol solution, drop the mixed solution on a circular porous glass fiber filter paper, dry it at 70 ° C, and wait for the photothermal catalyst to be evenly distributed on the glass fiber filter paper. Figure 4 In the reactor shown in the figure, H was introduced at a flow rate of 20 mL / min. 2 The reactor was heated to 400 °C at a rate of 10 °C / min by programmed temperature increase and kept at this temperature for 1 h to reduce the Ru oxide in the photothermal catalyst to metallic Ru. 2 The reactor was protected and cooled to room temperature. CO was introduced into the reactor at a total flow rate of 20 mL / min. 2 , H 2 、N 2 Mixed gas, the ratio is CO 2 :H 2 :N 2 =2:8:10. Adjust the xenon lamp illumination intensity to 2000mW / cm 2, irradiated on the surface of the photothermal catalyst, and carried out a long-term stability test for 12 hours under the monitoring of gas chromatograph.

[0072] Test results such as Figure 7 As shown, at 2000mW / cm 2 Under high-intensity simulated solar radiation, after 12 hours of long-term testing, Ru / ML-Ti 3 C 2 T x The photothermal catalyst can still maintain high catalytic activity, selectivity and stability, proving that it has the potential to be used in practical production in the future.

[0073] The present invention prepares Ru / ML-Ti by a simple one-step etching method and ion electrostatic adsorption method. 3 C 2 T x The photothermal catalyst has a unique multilayer structure and can realize a photothermal catalytic carbon dioxide process with high conversion, high selectivity and high stability. In addition, the present invention optimizes the design of the reactor in the photothermal catalytic test method, and further optimizes the photothermal catalytic performance of the photothermal catalyst.

[0074] Obviously, the above embodiments of the present invention are only examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. Those skilled in the art should understand that other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A method for preparing a photothermal catalyst, characterized in that: The following steps are involved: (1) Ti3AlC2 powder is mixed with hydrofluoric acid solution and etched to obtain a multilayer Ti3C2T with more than 15 layers of acidity x The solution was centrifuged to collect the precipitate, washed until neutral, and the washed precipitate was dispersed in water to obtain a multilayer Ti3C2T x Solution; wherein T is one or more of -O, -F and -OH; (2) Under the protection of an inert gas, a trivalent ruthenium salt and the multilayer Ti3C2T x The solutions are mixed, and the obtained mixed solution is dried to obtain the photothermal catalyst.

2. The preparation method according to claim 1, characterized in that: In step (1), the dosage ratio of the Ti3AlC2 powder to the hydrofluoric acid solution is (0.8-1.5) g: (10-15) mL.

3. The preparation method according to claim 1, characterized in that: In step (1), the etching time is 8-12 hours.

4. The preparation method according to claim 1, characterized in that: In step (2), the trivalent ruthenium salt is ruthenium trichloride.

5. The preparation method according to claim 1, characterized in that: In step (2), the mass of ruthenium element in the trivalent ruthenium salt accounts for x Multilayer Ti3C2T in solution x 1-10% of mass.

6. The preparation method according to claim 1, characterized in that: In step (2), the multilayer Ti3C2T x The concentration of the solution is 1-5 mg / mL.

7. The preparation method according to claim 1, characterized in that: In step (2), the drying treatment conditions are: vacuum drying at 70-80°C for 6-7h.

8. A photothermal catalyst prepared by the method according to any one of claims 1 to 7.

9. Use of the photothermal catalyst according to claim 8 in a carbon dioxide hydrogenation reaction.

10. The use according to claim 9, characterized in that: The performance of the photothermal catalyst is tested by using a photothermal catalytic testing device, which consists of a xenon lamp light source, a kettle reactor, a reaction gas inlet, a heating module, a heat preservation module, a reaction gas outlet and a temperature measurement module.

Citation Information

Patent Citations

  • Nickel hydroxide / titanium carbide photo-thermal catalytic material as well as preparation method and application thereof

    CN113441160A

  • Preparation method of photo-thermal catalyst capable of realizing carbon dioxide reduction

    CN118002165A